Honey lemon soda. 1 - Murata, Mayu (Yen Press, 2023)
"Uka Ishimori has one dream in life: to have fun in high school! As a self-avowed dense, stone-faced introvert who spent all of middle school hardening her heart against a daily barrage o bullying, breaking out of her shell is easier said than done. Luckily, she's not alone--Kai Miura, a classmate whose blond hair reminds her of the lemon soda he enjoys, has her back. Step by step, she endeavors to cast off the shadows of her past and reinvigorate her life!"--Back cover.